2021
DOI: 10.21203/rs.3.rs-197456/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does Having Comprehensive HIV and AIDS Knowledge Affect the Risky Sexual Behaviour of Young People in Sub – Saharan Africa: Pooled Analysis of Demographic and Health Surveys

Abstract: Background: Risky sexual behaviours (RSB) include all those behaviours such as multiple sexual unions, inconsistent use of condoms, or having sex under the influence of stimulants which have a greater propensity to exacerbate an individual’s vulnerability to unintended pregnancies and sexually transmitted infections including HIV/AIDS. This study explores the relationship between comprehensive knowledge on HIV and RSB among young people in sub-Saharan Africa (SSA).Methods: Data for this study were obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Consistent with a previous study, the current study revealed an alarming lack of HIV/AIDS knowledge and prevention among university students, and a low level of HIV knowledge was correlated with condomless sex [ 26 ]. Researchers have reported that knowledge about HIV/AIDS, as a form of self-empowerment, may influence a person’s perception of risk, which can lead to behavior change [ 27 , 28 ]. The current work suggests that providing comprehensive HIV/AIDS education in universities and even before college is critical.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with a previous study, the current study revealed an alarming lack of HIV/AIDS knowledge and prevention among university students, and a low level of HIV knowledge was correlated with condomless sex [ 26 ]. Researchers have reported that knowledge about HIV/AIDS, as a form of self-empowerment, may influence a person’s perception of risk, which can lead to behavior change [ 27 , 28 ]. The current work suggests that providing comprehensive HIV/AIDS education in universities and even before college is critical.…”
Section: Discussionmentioning
confidence: 99%
“…If they refused to use the condom, the HIV-infected youths would continue with sexual intercourse even without disclosure. A study showed that this was likely to happen especially with a casual partner [27][28][29][30]36,43,49].…”
Section: Attitudes Towards Safe Sexmentioning
confidence: 99%
“…6 Having intercourse with several sexual partners, having sex while under the influence of alcohol or drugs, failure to or inconsistent use of a condom, having sex with an unknown partner, usage of pornographic materials, and sexual coercion are examples of these activities. 7,8 Unsafe sexual practices may be associated with individual demographic factors, psychological factors and sociocultural factors. 9 Men are more likely to present with risky sexual behaviour than women.…”
Section: Introductionmentioning
confidence: 99%